The Role of Bowel Preparation in Colorectal Surgery: Results of the 2012–2015 ACS-NSQIP Data. Issue 4 (April 2019) - Klinger, Aaron L.; Green, Heather; Monlezun, Dominique J.; Beck, David; Kann, Brian; Vargas, Herschel D.; Whitlow, Charles; Margolin, David
Abstract : Objective: To analyze potential benefits with regards to infectious complications with combined use of mechanical bowel preparation (MBP) and ABP in elective colorectal resections. Background: Despite recent literature suggesting that MBP does not reduce infection rate, it still is commonly used. The use of oral antibiotic bowel preparation (ABP) has been practiced for decades but its use is also controversial. Methods: Patients undergoing elective colorectal resection in the 2012 to 2015 American College of Surgeons National Surgical Quality Improvement Program cohorts were selected. Doubly robust propensity score–adjusted multivariable regression was conducted for infectious and other postoperative complications. Results: A total of 27, 804 subjects were analyzed; 5471 (23.46%) received no preparation, 7617 (32.67%) received MBP only, 1374 (5.89%) received ABP only, and 8855 (37.98%) received both preparations. Compared to patients receiving no preparation, those receiving dual preparation had less surgical site infection (SSI) [odds ratio (OR) = 0.39, P < 0.001], organ space infection (OR = 0.56, P  ⩽ 0.001), wound dehiscence (OR = 0.43, P = 0.001), and anastomotic leak (OR = 0.53, P < 0.001). ABP alone compared to no prep resulted in significantly lower rates of surgical site infection (OR = 0.63, P = 0.001), organ space infection (OR = 0.59, P = 0.005), anastomotic leak (OR = 0.53, P = 0.002). MBP showed no significant benefit to infectious complications when used as monotherapy. Conclusions: Combined MBP/ABP results in significantly lower rates of SSI, organ space infection, wound dehiscence, and anastomotic leak than no preparation and a lower rate of SSI than ABP alone. Combined bowel preparation significantly reduces the rates of infectious complications in colon and rectal procedures without increased risk of Clostridium difficile infection. For patients undergoing elective colon or rectal resection we recommend bowel preparation with both mechanical agents and oral antibiotics whenever feasible.